GAP-43 slows down cell cycle progression via sequences in its 3′UTR - de Moliner, Karina Lorena (2015)
Growth-associated protein 43 (GAP-43) is a neuronal phosphoprotein associated with initial axonal outgrowth and synaptic remodeling and recent work also suggests its involvement in cell cycle control. The complex expression of GAP-43 features transcriptional and posttranscriptional components. However, in some conditions, GAP-43 gene expression is controlled primarily by the interaction of stabilizing or destabilizing RNA-binding proteins (RBPs) with adenine and uridine (AU)-rich instability elements (AREs) in its 3′UTR. Like GAP-43, many proteins involved in cell proliferation are encoded by ARE-containing mRNAs, some of which codify cell-cycle-regulating proteins including cyclin D1. Considering that GAP-43 and cyclin D1 mRNA stabilization may depend on similar RBPs, this study evaluated the participation of GAP-43 in cell cycle control and its underlying mechanisms, particularly the possible role of its 3′UTR, using GAP-43-transfected NIH-3T3 fibroblasts. Our results show an arrest in cell cycle progression in the G0/G1 phase. This arrest may be mediated by the competition of GAP-43 3′UTR with cyclin D1 3′UTR for the binding of Hu proteins such as HuR, which may lead to a decrease in cyclin D1 expression. These results might lead to therapeutic applications involving the use of sequences in the B region of GAP-43 3′UTR to slow down cell cycle progression.